Interpretation problems ln Habitat types listed ln annex I of council Dlrective 92/43/CEE - Portugal Mainland - Pinto-Gomes, Carlos (2020)
The Portuguese Sectoral Plan for lhe Natura 2000 Network includes 88 factsheets with ecological information about Portuguese habitat types listed in Habitats Directive. Produced by nationaJ experts - part of the former Lusitanjan Association of Phytosociology (ALFA) - these factsheets have been major tools for habitats interpretation and, ultimately, for the implementation of the Habitats Directive in Portugal.Despite their enormous scientific and operational value, in recent years several questions emerged about the interpretation of some of these habitats. These questions led to the growing realization that a review of the referred habitats factsheets is required. The review must comprise information to solve problems related to habitat interpretation, include recently produced phytosociological knowledge, and the discussion on the presence ofhabitat types not yet reported for Portugal. This review is essential for general clarification and standardization of procedures for land characterization and management, in particular inside the Natura 2000 Network. ln this presentation, some of the ca e that emerged during the execution of the 3rd National Report under Article 17, wiU be discussed. For example the inclusion of riparian Fraxinlls angu tifo/ia forests in habitat 91BO, the eligibility criteria for habitat 6510, the presence in Portugal of habitats 91FO, 7150, and other habitats not yet mentioned for our territory, will be discussed.